A novel functional crosstalk between DDR1 and the IGF axis and its relevance for breast cancer. Issue 4 (4th July 2018) - Belfiore, Antonino; Malaguarnera, Roberta; Nicolosi, Maria Luisa; Lappano, Rosamaria; Ragusa, Marco; Morrione, Andrea; Vella, Veronica
ABSTRACT: In the last decades increasing importance has been attributed to the Insulin/Insulin-like Growth Factor signaling (IIGFs) in cancer development, progression and resistance to therapy. In fact, IIGFs is often deregulated in cancer. In particular, the mitogenic insulin receptor isoform A (IR-A) and the insulin-like growth factor receptor (IGF-1R) are frequently overexpressed in cancer together with their cognate ligands IGF-1 and IGF-2. Recently, we identified discoidin domain receptor 1 (DDR1) as a new IR-A interacting protein. DDR1, a non-integrin collagen tyrosine kinase receptor, is overexpressed in several malignancies and plays a role in cancer progression and metastasis. Herein, we review recent findings indicating that DDR1 is as a novel modulator of IR and IGF-1R expression and function. DDR1 functionally interacts with IR and IGF-1R and enhances the biological actions of insulin, IGF-1 and IGF-2. Conversely, DDR1 is upregulated by IGF-1, IGF-2 and insulin through the PI3K/AKT/miR-199a-5p circuit. Furthermore, we discuss the role of the non-canonical estrogen receptor GPER1 in the DDR1-IIGFs crosstalk. These data suggest a wider role of DDR1 as a regulator of cell response to hormones, growth factors, and signals coming from the extracellular matrix.